Screening Tool for Mental Health Problems During COVID-19 Pandemic: Psychometrics and Associations With Sex, Grieving, Contagion, and Seeking Psychological Care - Morales Chainé, Silvia; Robles García, Rebeca; López Montoya, Alejandra; Bosch Maldonado, Alejandro; Beristain Aguirre, Ana Gisela; Treviño Santa Cruz, Claudia Lydia; Palafox, Germán Palafox; Lira Chávez, Isaura Angélica; Barragán Torres, Lydia; Rangel Gómez, María Gudelia (Frontiers in Psychology, 2022)
The COVID-19 pandemic has imposed a public mental health crisis. The aim of the paper was to determine the construct validity, reliability, and measurement invariance of a brief screening tool for mental health symptoms by sex, loss of loved ones, personal COVID-19 status, and psychological care-seeking during the COVID-19 pandemic. Furthermore, the aim involved to establishing a predictive pattern between the mental health variables. We worked with 27,320 Mexican subjects, with a mean age of 32 years old (SD=12.24, range= 18-80), 67% (18,308) women, 23.10% (6,308) with a loss-of-loves-ones, 18.30% (5,005) with COVID-19-condition, and 18.40% (5,026) seeking psychological care. Participants completed a questionnaire through a WebApp. We used the confirmatory factor analysis (CFA: through maximum likelihood to continuous variable data, as an estimation method), the invariance measurement, and the structural equational modeling (SEM) to provide evidence of the construct validity of the scale and the valid path between variables. Our findings suggested that the tool included the four dimensions of posttraumatic stress symptoms: intrusion/re-experimentation, avoiding, numbing, and hyperactivation, as well as depression, generalized anxiety, health anxiety, and somatization dimensions, which were confirmed through an 8-factor confirmatory factorial analysis. It was possible to describe the measurement invariance of scales because of the participants´ characteristics. Findings also indicated that women reported high generalized anxiety, hyperactivation, and depression. Those with the loss of loved ones reported a high level of intrusion/re-experimentation and health anxiety symptoms. Participants who reported a COVID-19-condition had presented high levels of generalized anxiety symptoms. Those who seek psychological care reported high levels of generalized anxiety, intrusion/re-experimentation, hyperactivation, and health anxiety symptoms. Our findings also indicated a prediction model between latent variables via a chi-square test and their fit indices through a structural equation modeling. Thus, we identified mental health problems in community and primary health care scenarios and through CFA of the PCL, PHQ, generalized anxiety, health anxiety, and somatization scales, adapted to be used during the COVID-19 pandemic. Further studies should ensure their follow-up and assess consistency with diagnoses of mental health disorders and evaluate the effect of the remote psychological help.